Compact UWB slotted pentagonal patch antenna for radar and communication - Mohd. Isa, Farah Nadia; Kamaludin, Nur H.; Abdul Malek, Norun Farihah; Mohamad, Sarah Yasmin (IEEE, 2019)
This paper presents a microstrip patch antenna that have an ultra-wideband (UWB) characteristics. The proposed antenna design is a slotted non-uniform pentagonal microstrip patch antenna with 1.6mm thickness of FR-4 as the substrate. Its small size of 30mm × 33mm achieved the miniaturization characteristics to fit on the surface of CubeSat. The antenna is simulated to resonate at 6.33GHz and operates at the range of frequency from 2.56GHz to 19.89GHz with bandwidth enhancement of 273.78%, while the fabricated antenna is measured to resonate between 3.10GHz to 12.74GHz and is optimum at 3.9GHz with bandwidth enhancement of 247.18%. This range covers most commonly frequencies for wide usage of radar and communication application such as earth observation, space weather forecasting, mobile communication etc. It manages to attain VSWR≤2 at the optimum frequency and have relatively good gain of 3.67dBi. The antenna is designed and simulated using Computer Simulation Technology (CST) Microwave Studio.